Shaken But Unruffled: Stories of Psychologically Distressed Public Secondary School Teachers - Olmedo, Armando Mazo; Gempes, Gloria Pacifico (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
Psychological distress is a global phenomenon that affects not only the psychological and physical well-being but also the profession of teachers around the world. The purpose of this multiple case study was to explore the experiences of psychologically distressed public secondary school teachers, their coping strategies, and insights they can share to their peers and to the academe in general. The participants of this inquiry were five female teachers from the public secondary schools of Davao del Norte division of Davao region, Philippines who experienced distress caused by school and personal stressors. Furthermore, informants underwent face-to-face in-depth interview. After a thorough analysis of the data using thematic, numeration and cross-case analysis procedures, it was found out that students’ misbehavior was the most common cause of teachers’ distress. On the coping strategies employed by them, it also came out that controlling the emotion was their most usual coping strategy against their distressful experiences. Moreover, teaching as both profession and ministry was the strongest insight. Finally, this study has provided some important implications on how to address the said phenomenon, suggested relevant insights for meaningful learning, and considered vital related topics which necessitate future undertakings.